2018
DOI: 10.1016/j.bbabio.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial denitrifying nitric oxide reductases and aerobic respiratory terminal oxidases use similar delivery pathways for their molecular substrates

Abstract: The superfamily of heme‑copper oxidoreductases (HCOs) include both NO and O reductases. Nitric oxide reductases (NORs) are bacterial membrane enzymes that catalyze an intermediate step of denitrification by reducing nitric oxide (NO) to nitrous oxide (NO). They are structurally similar to heme‑copper oxygen reductases (HCOs), which reduce O to water. The experimentally observed apparent bimolecular rate constant of NO delivery to the deeply buried catalytic site of NORs was previously reported to approach the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…The movement of a molecule through a protein may involve not only structural perturbations of the protein, from breathing motions of lining amino acids 4952 to largescale conformational changes, 5357 but also the dynamics of the passing molecule (substrate or ligand). 58 Although the pores of CsoS1A and CcmK4 are relatively wide to accommodate a free passage of small molecules, such as HCO3, CO 2 and O 2 , the calculated ΔG profiles indicated that such molecules cannot pass through easily.…”
Section: Resultsmentioning
confidence: 99%
“…The movement of a molecule through a protein may involve not only structural perturbations of the protein, from breathing motions of lining amino acids 4952 to largescale conformational changes, 5357 but also the dynamics of the passing molecule (substrate or ligand). 58 Although the pores of CsoS1A and CcmK4 are relatively wide to accommodate a free passage of small molecules, such as HCO3, CO 2 and O 2 , the calculated ΔG profiles indicated that such molecules cannot pass through easily.…”
Section: Resultsmentioning
confidence: 99%
“…While NORs use exclusively heme b and bind iron (Fe B ) in their nonheme center with a conserved 3His-1Glu first coordination sphere, HCOs may host different types of hemes (e.g., heme o, a, and b) and bind copper (Cu B ) with a tripodal 3His coordination sphere, depending on the organism [73]. Thorough mechanistic studies have been performed for these two homologous classes of proteins [74][75][76][77][78][79] and few details are still under debate [80][81][82]. Nonetheless, in both cases protein matrix is able to promote selectivity of one metal over the other and to drive the correct inter-metal distance along the various oxidation states of the metal and reaction intermediates [83].…”
Section: Figmentioning
confidence: 99%
“…S6), it may compensate for the loss of Val 485 to continue shuttling NO. A computation study on Pa cNOR investigated NO diffusion and found that several migration pathways exist (termed dominant and alternate), where migration of NO is ~10-fold lower using the alternate route than using the dominant pathway ( 49 ). Several of the routes include conserved residues found in our tunnel analysis (Val 285 , Ile 484 , Leu 336 , and Leu 487 ), which may suggest a generic role in NO transport across NORs.…”
Section: Discussionmentioning
confidence: 99%